Validation of the Personal Wellbeing Index (Pwi) in Vulnerable Users of Health Care Services in Santiago, Chile [Validación del Índice de Bienestar Personal (Pwi) en Usuarios Vulnerables de Servicios de Salud en Santiago, Chile] - Oyanedel-Sepulveda, J (Sociedad Medica de Santiago, 2015)
Background: Personal well-being calculates quality of life in terms of the necessary conditions required to live well. Aim: To validate the Personal Wellbeing Index (PWI) in a representative sample of vulnerable users of the public health system in Santiago, Chile. Material and Methods. A probabilistic and multistage sample consisting of 400 individuals aged 44 ± 18 years (61% females) belonging to the lower income group of the National Health Fund (FONASA), residents of Gran Santiago was surveyed. Internal consistency and correlation between items and scale were examined. Structure was analyzed through confirmatory factor analysis. Results: The seven-item PWI is a good indicator of subjective well-being in the population under study, considering internal consistency, factor loadings, relation with overall life satisfaction and goodness of fit. The indicators mostly associated with personal well-being are the socioeconomic level followed by relationships with the community, health conditions and achievements. Conclusions: The 7-item version of the PWI is suitable for application in vulnerable health service users. © 2015, Sociedad Medica de Santiago. All Rights Reserved.